APPLYING GAMIFICATION PRINCIPLES THROUGH THE DESIGN THINKING FRAMEWORK FOR DEVELOPING A MIXED REALITY EDUCATIONAL GAME IN NUMERACY LEARNING - Gumulya, Devanny; Suhanto, Yosefin (Ide dan Dialog Desain Indonesia (Idealog), 2023)
Numeracy is one of the most crucial literacy skills to develop at a young age. These skills are taught in the classroom through mathematics. According to several studies from the Programme for International Student Assessment (PISA), students' mathematical abilities in Indonesia remain low when compared to other literacy skills. This subject is often perceived as challenging and tedious. Furthermore, the concept of teaching numeracy skills cannot be approached abstractly initially, especially for children who require tangible objects for manipulation. The research employed a design thinking approach, encompassing diverse methodssuch as observation, interviews, questionnaires, literature review, direct observations involving children, and problem analysis. This project aims to create educational media infused with gamification elements such as points, badges, levels, and leaderboards. The final product of this design project is an educational toy named “LIGI” seamlessly integrated with a mobile app, referred to as "mixed reality." The product's dif iculty level can be tailored based on the abilities of each individual child. Moreover, in-game navigation employs the perceptual user interface (PUI), involving device movements and spoken commands to provide an interactive experience. This study ef ectively demonstrates the application of gamification elements in the development of mixed reality educational games, aimed at helping children understand and practice numeracy skills in a more interactive and innovative manner, following the design thinking framework stages of empathize, define, ideate, prototype, and testing. The study provides valuable guidance for product designers interested in creating impactful mixed reality educational games by integrating gamification principles. The authors stress the importance of integrating gamification elements during the ideate stage and conducting timely testing with children to comprehend their preferences and enjoyment. Keywords: educational toy, mixed–reality, gamification, perceptual userinterface